Generalized principles for the descriptor-based design of supported gold catalysts - Rekhi, Lavie (2024)
We postulate generalized principles for determining catalytic descriptors like the adsorption energy of CO*, across interfacial active sites of gold catalysts having varying coordination numbers and differing proximity to the support. These principles are derived using Density Functional Theory (DFT) calculations, linear scaling relationships, and an electronic structure analysis. Considered supports include two-dimensional (2D) and three-dimensional (3D) carbides and nitrides, doped MgO, and MoS2. We show that the stability of gold atoms, across different coordination numbers, is linearly correlated to the adsorption energy of CO* through site-specific scaling relationships. As per definition, the slopes of these site-specific scaling relationships portray the extent of structure-sensitivity of CO* adsorption. This structure-sensitivity indicates the dependence of adsorption energies of CO* on the coordination number of the Au sites. The site-specific scaling relationships inform that interfacial perturbations are localized at the metal layer proximal to the interface. These perturbations are moreover strongest at low-coordinated gold sites. Interestingly, the interaction energies between adsorbates at higher coverages are insensitive to interfacial perturbations, further demonstrating the localized nature of metal-support interactions. Our interpretations of the slopes of site-specific scaling relationships indicate that the structure-sensitivity of interfacial gold sites is determined by the extent of interfacial charge transfer. The CO* adsorption energy is structure-insensitive on supports that induce a negative charge on interfacial gold atoms. This structure-sensitivity proportionally increases with the progressively increasing positive charge on interfacial gold atoms. Such charge transfer-dependent structure-sensitivity is rationalized using Lewis acid-base interactions. We demonstrate that tuning the adsorption energy of CO* by manipulating interfacial charge transfer can endow a Cu-like reactivity to interfacial Au sites for CO2 electro-reduction. By melding the generalized principles derived in this study, we synthesize a scheme for determining site-specific catalytic descriptors at interfacial active sites of supported gold catalysts.